Physical Characteristic and Acceptability of The Keropok Crackers from Different Straches - Haryadi Haryadi (Indonesian Food and Nutrition Progress, 1994)
Keropok crakcers made of six different starches (tapioca, maize, arrowroot, cana, Arenga sago and Metroxylon sago) resulted in different extents of expansion, but this did not correlate with the amylopectin content. Keropok crackers with greater expansion was not neccesarilly more hygroscopic.Crispiness acceptability increased with increasing expansion of volume. Higher amylopectin content of the starch gave more acceptable flavor of the cracker